A study on phase equilibria in the CaO-Al2O3-SiO2-“Nb2O5”(5 mass pct) system in reducing atmosphere - Yan B.; Guo R.; Zhang J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Phase equilibria in 5 mass% “Nb2O5” plane of CaO-Al2O3-SiO2-“Nb2O5” system at 1873 K in an oxygen partial pressure of 1.78×10-6 Pa have been investigated through isothermal equilibration and quenching followed by EPMA examinations. In order to characterize the effect of niobium oxide on the phase relationship of the CaO-Al2O3-SiO2 system, Nb2O5-containing and Nb2O5-free samples with the same CaO/Al2O3/SiO2 weight ratio were investigated simultaneously. The ratios of CaO/Al2O3/SiO2 were selected from the CaO•2Al2O3-liquid two-phase equilibrium region in the CaO-Al2O3- SiO2 system at1873 K. It was found that the adding of 5 mass% Nb2O5 to the CaO-Al2O3-SiO2 system caused the original CaO•2Al2O3-liquid equilibrium to become three different new equilibria. The three equilibria were single liquid phase, CaO•6Al2O3-liquid and gehlenite-CaO•2Al2O3-liquid equilibrium respectively. The gehlenite phase may be a new solid solution of 2CaO•Al2O3•SiO2 and NbOx with melting point higher than 1873 K.